The Commodification of Information Commons: The Case of Cloud Computing - Filippi, Primavera De; Vieira, Miguel Said (Science and Technology Law Review, 2014)
Internet and digital technologies allowed for the emergence of new modes of production involving cooperation and collaboration amongst peers (peer-production). In contrast with traditional models of production oriented towards the maximization of profits, these alternative modes of production are, more often than not, oriented towards the maximization of the common good. To ensure that content will always remain available to the public, the output of production is often released under a specific regime that prevents anyone from subsequently turning it into a commodity (the regime of information commons). While this might reduce the likelihood of commodification, information commons can nonetheless be exploited by the market economy. Indeed, since they have been made available for use by anyone, large online service providers can indirectly benefit from the commons by capturing the value derived from it. While this is not a problem per se, problems arise when the exploitation of the commons by one agent is likely to preclude others from doing the same—often as a result of commodification. This is especially true in the context of cloud computing, where the content holder has become as powerful as, if not more powerful than the copyright owner. Nowadays, regardless of their legal status, information commons are increasingly controlled by large corporations who can precisely define the manner in which they can be used or accessed. Digital communities need to be aware of these risks. This Article proposes a theoretical and normative exploration of these issues based on an analysis of recent trends in cloud computing. It argues that, in order to reduce the likelihood of commodification but still benefit from the advantages offered by cloud computing, digital communities should rely on decentralized platforms based on peer-to-peer architectures, thereby escaping from the centralized control of large service providers while nonetheless preserving the autonomy of the commons they produce.